(untitled) (Al-Academy, 2025)
In the current study (generative design and its role in developing the design of cans and packaging), the researcher studied generative design and its role in developing the field of can and packaging design, which saves the effort and time needed to develop it, by using the designer’s scientific abilities in directing those models and applications and using appropriate standards according to the scientific foundations studied from the inputs. Which contributes to enriching the design of these boxes and covers. To demonstrate this, the researcher experimented with working on the Midjournal generative intelligence design program, which is considered one of the most important generative design programs in designing packaging for perfumes from well-known brands. The researcher relied on the statistical approach in extracting sample results through... A questionnaire form through which the experience was evaluated.